PEMANDANGAN ALAM SUMATERA BARAT DALAM SENI LUKIS NATURALIS - WAHYU NOVIANRI, Drs. Abd Hafiz, M.Pd., Drs. Efrizal, M.Pd. (Serupa The Journal of Art Education, 2019)
The purpose of this final projectis to visualize the natural landscape of West Sumatra. The method usd or this final project was the preparation, elaboration, synthesis, realization of the concept, and settlement. The visualized project are : (1)Koto Tinggi, (2) Nirwana Beach, (3) Taluak Sikulo I, (4) Tabiang Takuruang, (5) Maninjau Lake, (6) Harau Valley, (7) Lubuak Hitam Waterfall, (8) Kelok 9, (9) Taluak Sikulo II, (10) Lubuak Nyarai Waterfall.Keywords: Landscape Natural, Naturalist, Painting